The effect of price, service quality on user satisfaction for maxim users in city Palembang - Febriyanti, Sania Eka; Widagdo, Herry (Universitas Multi Data Palembang, 2023)
The purpose of the study is to analyze the effect of price, service quality,brand image and brand trust on user satisfaction for maxim users in PalembangCity. Another objective is to analyze the factors consisting of price, servicequality, brand image, and brand trust on user satisfaction for maxim users inPalembang city simultaneously and method used for data with 160 samples. Thetype of research used is descriptive quantitative research. And based on the resultof the price, service quality, brand image and brand trust has a significantinfluence on user satisfaction.